2003
DOI: 10.1023/a:1025453500148
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Marimastat is a broad-spectrum matrix metalloproteinase (MMP) inhibitor that inhibits almost all major MMPs, key enzymes in gastric cancer invasion and metastasis. We investigated the ability of marimastat to inhibit tumor angiogenesis in the severe combined immuno-deficient (SCID) mouse/human gastric cancer model of peritoneal dissemination. A human stomach adenocarcinoma cell line, TMK-1, was injected intraperitoneally into SCID mice. On the 7th day after tumor inoculation, the administration of marimastat (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Angiogenesis was evaluated by an index of MVD described in previous reports. , The tumor sections (5 μm) prepared for immunohistochemistry were stained with CD31 to quantify the vessel density inside tumors. In brief, the paraffin-embedded sections were prepared for antigen retrieval after being dewaxed, rehydrated, and microwaved.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiogenesis was evaluated by an index of MVD described in previous reports. , The tumor sections (5 μm) prepared for immunohistochemistry were stained with CD31 to quantify the vessel density inside tumors. In brief, the paraffin-embedded sections were prepared for antigen retrieval after being dewaxed, rehydrated, and microwaved.…”
Section: Methodsmentioning
confidence: 99%
“…Marimastat (MATT), a broad-spectrum synthetic enzyme inhibitor, can achieve greater than 50% enzyme inhibition of collagenases, gelatinases, and MMPs, even at a nanomolar concentration; it mimics MMP substrates and thus displays competitive and potent, but reversible, suppression. ,, MATT inhibits tumor progression by inhibiting metastasis. Nevertheless, it is not cytotoxic and therefore cannot kill tumor cells, which dramatically compromises its antitumor efficacy.…”
mentioning
confidence: 99%
“…For example, Yanagihara et al (22) reported that a cDNA microarray analysis demonstrated dramatic upregulation of MMP-1 (ratio: 29.63) in the 44As3 gastric cancer cell subline which shows frequent metastasis to the peritoneum, in comparison to parental HSC-44PE cells. In addition, previous studies reported that an MMP inhibitor reduced the peritoneal dissemination of human gastric cancer cell lines in mice (18,23). Taken together, our results and the previous findings indicate that the upregulation of MMP-1 expression following the loss of HIF-1α might be an important step in the development of peritoneal dissemination from MKN45 and MKN74 gastric cancer cells.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, marimastat decreased the tumour growth in mice injected with MGLVA1 human gastric tumours (Wada et al 2003). In the clinical setting a phase I study of marimastat showed an acceptable safety proWle in 35 patients with advanced GC or carcinoma of the GEJ.…”
Section: Matrix Metalloproteinase (Mmp) Inhibitorsmentioning
confidence: 99%